Social influence, performance expectancy, and price value as determinants of telemedicine services acceptance in Chile - Cristian Vidal-Silva; Aurora Sánchez-Ortiz; Jorge Serrano-Malebrán; Vanessa Arriagada; Moisés Flores; Mónica Godoy; Cristopher Vargas (Heliyon, 2024)
Medicine is a discipline based on and nurtured by scientific research and technological development. The use of health services supported by information technology is increasing worldwide, and Latin America is no exception. Factors such as needing more specialists in peripheral cities, large geographic areas, and socio-cultural aspects limit the possibility of receiving timely and quality medical care services. Information Technology (IT) for health purposes, such as e-health, is a cost-effective solution for equitable access to quality healthcare services and optimization of the rising associated costs. As an e-health service, telemedicine facilitates and mediates distance communication between the patient and medical staff. Even though Latin America is at the beginning of the development of telemedicine, it would have a relevant impact, given the geographic and socioeconomic conditions of the population in this part of the world. Drawing on the extended Unified Theory of Acceptance and Use of Technology (UTAUT2) theory, we developed a theoretical model to identify the latent factors influencing the public acceptance of telemedicine and examined their interrelationships. A survey questionnaire was designed and administered to 391 residents in Antofagasta, a mine region of Chile. After that, structural equation modeling was employed to analyze the survey data. The results reveal that the UTAUT2 factors' performance expectancy, social influence, and price value significantly impact the intention to use (R2 = 0.693). Additionally, the model presented a good fit. This study enriches the existing theoretical research on the acceptance of telemedicine services and offers insights into understanding and managing technology in the Chilean health sector.